Penerapan Pembelajaran Mendalam Mata Kuliah Al-Islam Dan Kemuhammadiyahan Untuk Meningkatkan Pemikiran Kritis Dan Internalisasi Nilai Islami Mahasiswa - Basir B; Ayyub Ht, Andi Muh; Muh. Rivai Khalik (JBKPI: Jurnal Bimbingan dan Konseling Pendidikan Islam, 2025)
This study aims to describe the application of deep learning in Al-Islam and Kemuhammadiyah (AIK) courses, as well as analyze its impact on improving students' critical thinking skills and internalizing Islamic values. This study uses a literature study method approach with narrative synthesis analysis of relevant national and international references using research data of at least 23 articles that are freely accessed on topics discussed by research objects, research methodologies and using data references from the last 10 years. Data collection techniques are carried out with keywords, and presented in a table with descriptive analysis techniques. From the results of the literature data study, the results of the study show that the application of deep learning in increasing critical thinking and internalizing Islamic values to students in AIK courses has an impact on the improvement of critical thinking and the practice of Islamic values of students in the Muhammadiyah Higher Education environment.